PENGARUH KUALITAS PELAYANAN DAN PENGGUNAAN INSTAGRAM TERHADAP MINAT BELANJA ONLINE SHOPEE DAMPAKNYA PADA LOYALITAS PELANGGAN: (Studi Kasus Pegawai Balai Pengamanan Fasilitas Kesehatan (BPFK) Jakarta dan Unit Pelaksana Fungsional Pelayanan Fasilitas Kesehatan (UPF-PFK) Palembang) - Rosmegawati; Sumihar M. L. Tobing; Marlina (Jurnal Multidisiplin Borobudur, 2023)
This study aims to determine the effect of service quality on the use of Instagram on interest in shopping online at Shopee and its impact on customer loyalty. The independent variable is service quality and the dependent variable is customer loyalty. The method in this study uses a quantitative method with a Likert scale. The data used are primary and secondary data. Primary data was obtained by distributing questionnaires as the instrument. For a sample of 117 respondents who were obtained from employees of the Jakarta Health Facility Security Center (BPFK) Office and Palembang Health Facility Service Functional Service Unit (UPF-PFK) who actively use the Shopee application for online shopping. The analysis used with the help of SPSS version 23.0. The results of this study indicate that all service quality variables have a significant effect on the interest in shopping online at Shopee on customer loyal. The results of this study indicate that the variable service quality has a positive and significant effect on customer loyalty, the use of Instagram has a positive and significant effect on customer loyalty, interest in online shopping has a positive and significant effect on customer loyalty and customer loyalty has a positive and significant effect on quality services in the interest of online shopping Shopee.